Flipped Classroom: Effect on the Academic Performance and Motivation of Grade 8 Students in Mathematics - Baybayan, Jericho Y.; Cabanes, Aileen (Future Science / FSH-PH Publications, 2024)
Teachers nowadays are being challenged due to continuous decrease in the analytical and numerical ability of the students. Strategies were continuously studied by teachers to address such concern answering also questions such as how students perceived flipped classroom setting as an aid to the teaching learning process. This study utilized descriptive quasi-experimental design through 189 Grade 8 students where it had found out that in terms of the Pre-Assessment results, most of the students are in the “did not meet expectation” category but still are motivated in terms of Performance Task Making, Problem Solving, Classroom Participation and Examination. In terms of the post-assessment results, most of the students are in the “satisfactory” category and are highly motivated in terms of Performance Task Making, and motivated in Problem Solving, Classroom Participation and Examination. There is a significant improvement in the academic performance of the students where post-assessment results showed higher mean score than the pre-assessment results. There is a positive significant relationship between Performance and Level of Motivation. The main issues and concerns of the students in the implementation of flipped classroom is the slow internet connection at school and at home. Thus, concludes that indeed Flipped Classroom Learning is a way to better improve education identifying the effect on the academic performance and motivation of students in mathematics noting also that internet connection plays a crucial role in this type of learning setting.